Hypothyroidism monitoring and control during the first trimester of pregnancy in Catalonia - Tena Vivó, Glòria; Cunillera Puértolas, Oriol; Albareda Riera, Mercè; Parellada Esquius, Neus; Isidro Albaladejo, Mònica; Rodríguez Palomar, Gemma; Palmero Aliste, Silvia; Vila, Lluís (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to describe hypothyroidism monitoring and control during the first trimester of pregnancy in women with known hypothyroidism in Catalonia.Materials and methodsPregnancies registered in primary care in Catalonia between 2014 and 2016 were retrospectively studied. Women with hypothyroidism were selected for the study. Hypothyroidism was defined if, on the date of the last menstrual period (LMP), there was an updated thyroid hormone prescription (code ATC H03AA -levothyroxine) or any of the following active diagnostic codes: ICD-10: E02, E03, E89.0. To evaluate hypothyroidism monitoring and control, thyrotropin (TSH) tests during the first trimester of pregnancy were considered and categorized according to the reference values of each laboratory.ResultsOut of 111,811 pregnancies, 5,574 had known hypothyroidism. TSH was evaluated in 3,158 (56.65%) of them. The TSH values were within the recommended ranges in 1,146 (36.3%) of the cases, being low abnormal in 53 of them (1.7%) and high abnormal in 1,959 (62%).ConclusionTSH testing was not evaluated in almost half of the pregnant women with known hypothyroidism in primary care services in Catalonia during the pregnancy first trimester. Among those tested, more than two-thirds had TSH levels outside the target range. This means that it is essential to improve the management of hypothyroidism during the first trimester of pregnancy in Catalonia.